Special forces in action Iraq, Syria, Afghanistan, Africa, Balkans - Stilwell, Alexander (Amber Books, 2015)
In 1991, Coalition special forces were active deep inside Iraq, hunting down SCUD missile launchers before they could be fired. In 2011, US Navy SEALs were responsible for the assassination of the world's most wanted terrorist, Osama bin Laden